Почему иудаизм не получил распространения в Хазарском каганате (в поисках ответа) - Флёров, В.С. (Степи Европы в эпоху средневековья, 2012)
Материальные памятники VI-X вв., которые можно было бы достоверно связать с иудейским культом, на территории Хазарии практически отсутствуют. Эту ситуацию можно считать парадоксальной, если учесть, что в до-хазарский период в Северном Причерноморье, в том числе на Боспоре и в Крыму, памятники, безусловно свидетельствующие о присутствии евреев, хорошо известны: более 100 надгробий с иудейской символикой, традиционной для всего античного мира (менора, лулав, этрог), надписями на греческом и еврейском. Among the most challenging problems of the Khazar studies is the question of in how much Judaism was spread in Khazaria. The problem is that in spite of indisputable written evidence there is no archaeological proof of the presence of Jews and proselytes in the kaganate except for individual and rather dubitable finds. No burials by the Jewish rite were found. The climate and especially the absence of towns impeded settling of Jews in the steppes and forest-steppes of Khazaria. The spread of Judaism was hampered by the fact that the basic concepts of Judaism were extremely complicated to be translated into the local languages. Judaism involved rules for behaviour in everyday life which were unacceptable for the population of the kaganate. The problem of marriages between Jews and pagans was inevitable. As a result proselytes came to be isolated.